The Cognitive Dimension and the Affective Dimension in the Patient’s Experience - Reinares-Lara, Pedro; Rodríguez-Fuertes, Alfredo; Garcia-Henche, Blanca (Frontiers in Psychology, 2019)
This article deals with the experience of a particular client that of the health services, that is, the patient. For the assessment of the patient's experience, satisfaction questionnaires are usually applied. However, these tools offer only a cognitive evaluation, not being able to pick up the affective dimension of the experience. The objective of this study was to verify the relationship between the cognitive dimension of the experience collected through questionnaires, and the affective dimension, from the analysis of neurophysiological data. We propose a novel methodology that integrates the physiological data collected by the facial expressions analysis to identify the emotions of the patients. A first qualitative approach was carried out to define a patient journey, which was recorded on video and later used in the experiment. The experiment consisted of collecting information from the participants while viewing the videographic materials by means of two techniques: the traditional questionnaires, and the Facial Expression Analysis (FEA), to finally compare the results provided by each one. The results show that there is no relationship between emotional valence reported by questionnaires and the neurophysiological data. This difference reflects the two different dimensions of the experience, one cognitive and the other affective. Both facilitate the understanding of patient satisfaction.